Deposition, characterization, and device fabrication of GaN and AlN based thin film materials - Ashraf Uddin. (2008)
With the wide appealing application of GaN in electronic and optoelectronic device, many researchers had come out with innovative ways of preventing the cracks and reduction of strain at the interface. This is due to the different in CTE and approximately 16.9% lattice mismatch between GaN and Si substrate. One of the most common and effective method was through the insertion of AlN as an inter-layer buffer material. This was adopted during the sample preparation stage. Cracks were not seen on any GaN film of the samples which is a good start for the possible application in future.